Effect of diet and sex-sorting on growth and gonad development in farmed South African abalone, Haliotis midae - Ayres, Devin William Philip (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Abalone, Haliotis midae, farmers in South Africa that feed formulated diets reported a periodic drop in abalone growth during periods of increased gonad development. A large drop in abalone biomass was noticed after presumed spawning events. This study was aimed to determine the effect of diet and sex-sorting on gonad development in abalone. Experiments were conducted on a commercial abalone farm from July 2012 to the end of June 2013. Isonitrogenous and isoenergetic diets were formulated with two protein sources. A fishmeal and soybean meal (S-diet) diet and a fishmeal only (F-diet) diet were fed to abalone (50 - 70 g abaloneâ »Â¹) over 12 months. Weight and length gain, gonad bulk index (GBI), visceral index (%) and meat mass index (%) were determined monthly and seasonally. A histological study on the female gonads was conducted. This study also included an experiment to test the effect of sex-sorting (70 - 80 g abaloneâ »Â¹) on growth and body composition with treatments including males (M), females (F) and equal numbers of males and females (MF). Weight gain and length gain were faster in S-diet-fed abalone (RM-ANOVA, F â‚ â‚ , â‚ â‚†â‚Ž = 7.77, p = 0.01; F â‚ â‚ , â‚†â‚‰â‚Ž = 49.9, p < 0.001, respectively). Gonad development was significantly affected by the inclusion of soybean meal with S-diet-fed abalone showing higher GBI-values than F-diet-fed abalone (RM-ANOVA, F â‚ â‚ , â‚ƒâ‚ƒ)= 16.22, p = 0.0003). Male abalone had higher GBI-values than females (RM-ANOVA, F â‚ â‚ , â‚ƒâ‚ƒâ‚Ž = 39.87, p < 0.0001). There was no significant difference in average feed conversion ratio (FCR) between diets over time (RM-ANOVA, F â‚ â‚ , â‚‚â‚ â‚Ž = 0.008, p = 0.97). However, average FCR-values were significantly highest between November 2012 and March 2013, the presumed spawning season. The visceral mass (gut and gonad) as a proportion of whole mass (visceral index, %) was significantly higher in abalone fed the S-diet (RM-ANOVA; F â‚ â‚ , â‚†â‚‰â‚Ž = 68.06, p < 0.0001). There was no difference in meat mass index (%) between diets for both male and female abalone (RM-ANOVA; F â‚ â‚‡, â‚‚â‚„â‚ˆâ‚Ž = 0.80, p = 0.60; F â‚ â‚‡, â‚‚â‚„â‚ â‚Ž = 1.7, p = 0.11,respectively). Meat mass index significantly decreased from September 2012 to February 2013 coinciding with the period of high GBI-values. The distribution of oocyte maturity stages differed between diets. The majority of oocytes within S-diet-fed abalone were fully mature stage 8 oocytes compared to a majority of stage 7 oocytes in F-diet-fed abalone. Histology corroborated peaks in GBI-values for abalone fed both diets. There was no significant difference in growth, GBI, visceral index (%) and meat mass index (%) between abalone sorted into monosex and mixed-sex populations. Thus, the presence of the opposite sex did not have an effect on growth and gonad mass in H. midae. The phytoestrogens daidzin, glycitin, genistin, daidzein, glycitein and genistein were present in soybean meal and only traceable amounts were found in the F-diet. This study provided evidence that soybean meal present in formulated feed affected growth and gonad development in H.midae. The difference in the distribution of the maturity stages of oocytes was affected by diet. Sex-sorting abalone into monosex and mixed-sex populations had no influence on weight and length gain and gonad development.
Keywords: Haliotis midae -- South Africa; Haliotis midae fisheries -- South Africa; Abalone culture -- South Africa; Abalones -- Physiology -- South Africa; Abalones -- South Africa -- Growth; Abalones -- Feeding and feeds -- South Africa